Oromotor Dyspraxia in Benign Childhood Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
A six year old right handed boy with prolonged intermittent drooling, oromotor dyspraxia, and benign childhood epilepsy with centrotemporal spikes is reported from the Departments of Pediatrics and Neurology, Centre Hospitalier, Universitaire Vaudois, Lausanne, Switzerland.